Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 1977 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Ambrosia artemisiifolia L.", "HasGeospatialIssue is false", "Geometry POLYGON((-30.94 -4.81,-30.94 79.26,-170.51 79.26,-170.51 -4.81,-30.94 -4.81))" ] } The dataset includes 1977 records from 76 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0093128-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences